The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2320/matertrans.m2013363
|View full text |Cite
|
Sign up to set email alerts
|

Defects Modification of TiB<sub>2</sub>&ndash;TiC Composite Phase Coating Resistance Spot Welding Electrode via Friction Stir Processing

Abstract: In this work, surface modification was carried out using friction stir processing (FSP) technique to investigate on the electro-spark deposited (ESD) TiB 2 TiC coated electrode caps for resistance spot welding. The morphology, microstructure, phase composition and resulting mechanical properties of the electrode were examined and characterized. The results showed that treatment with FSP significantly reduced the number of cracks formed on TiB 2 TiC coating and enhanced the interfacial binding force between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…This is in agreement with Y. Morisada and co-workers' work. 20) Additionally, the coarse columnar grains of copper alloy substrate that observed in Fig. 2 (a) are instable, with temperature of the substrate increased, they spontaneously transfer into the equiaxed microstructure.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…This is in agreement with Y. Morisada and co-workers' work. 20) Additionally, the coarse columnar grains of copper alloy substrate that observed in Fig. 2 (a) are instable, with temperature of the substrate increased, they spontaneously transfer into the equiaxed microstructure.…”
Section: Methodsmentioning
confidence: 95%
“…912) The recrystallization temperature of pure Ni is about 632°C. 24) Our previous work 20) reported that the substrate temperature generated by FSP didn't exceed the softening point, which indicates that the Ni within the coating may be recrystallized by severe plastic deformation during the FSP, resulting in the elimination of cracks. This is in agreement with Y. Morisada and co-workers' work.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…FSP for microstructure refinement has also been applied to coatings, including Al-Cr-O plasmasprayed composites [24], Al-Al 2 O 3 cold-sprayed composites [25], electro-spark-deposited TiB 2 -TiC composite [26], flame thermal-sprayed Ni-Cr-Al alloy [27], and cemented carbide layers [28]. Other benefits also have been attributed to FSP, such as improved liquation cracking resistance in the heat-affected zones of nickel-based alloys [29], and consolidation of sintered microstructures in powder metallurgy-based metal matrix composites [30].…”
Section: Potential For Microstructure Modificationmentioning
confidence: 99%